Bioacoustics characterization of some anatolian endemic and sub-endemic Katydids (Orthoptera; Tettigoniidae; Bradyporinae, Phaneropterinae and Tettigoniinae) - Taylan Mehmet Sai̇t; Mol, Abbas; Sevgi̇li̇ Hasan; Şi̇ri̇n Deni̇z (Zootaxa, 2019)
Seventeen endemic and three sub-endemic species belonging to three subfamilies of Tettigoniidae (Orthoptera: Bradyporinae, Phaneropterinae and Tettigoniinae) were sampled during field trips throughout different regions of Anatolia between 2015 and 2018 (except one taxon). Acoustic parameters of these 20 bush-cricket species affiliated to 12 genera (Apholidoptera, Bradyporus, Decticus, Eupholidoptera, Parapholidoptera, Pezodrymadusa, Pholidoptera, Polysarcus, Psorodonotus, Squamiana, Uvarovistia and Yalvaciana) have been described for the first time in this study. Bioacoustical analysis shows that male calling songs are species-specific for the genera Bradyporus, Parapholidoptera, Pholidoptera, Apholidoptera, Uvarovistia and Psorodonotus. However, there are no distinct differences among species of the genus Pezodrymadusa. Moreover, our additional data on genus Eupholidoptera indicate that there are some different song patterns within the genus. The song description of Uvarovistia zebra presented here is the second bioacoustics data on this genus. The acoustical analyses data support the morpho-species hypothesis of Psorodonotus suphani Taylan & Şirin, 2014, which is known from Süphan Mountain (Bitlis province, Eastern part of Turkey) and reject Kaya & Çıplak (2017), which recommended it as synonym to P. caucasicus (Fischer von Waldheim, 1846) (commonly known as a Black Sea Region species).